EVALUASI PENGGUNAAN TERAPI ANTIHIPERTENSI TERHADAP TEKANAN DARAH PRA-DIALISIS PADA PASIEN RAWAT JALAN DENGAN END STAGE RENAL DISEASE (ESRD) YANG MENJALANI HEMODIALISIS RUTIN DI RS PKU MUHAMMADIYAH YOGYAKARTA - , Fitriani, Dr. Agung Endro Nugroho, M.Si., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Hypertension and chronic kidney disease (CKD) are the two kinds of disease that are related each others. Hypertension is not only a major cause of kidney failure but also becomes a problem of dialysis patients. The prevalence of hypertension is estimated to occur in 80% of the hemodialysis population. Hypertension increases the risk of cardiovascular disease. Cardiovascular disease and complications are known as the major cause of morbidity and mortality among ESRD patients. In hemodialysis population, the target of pre-dialysis blood pressure is <140/90 mmHg and for the post-dialysis is <130/80 mmHg. This research aims to determine the relationship between the compliance levels of patients in antihypertensive medication towards the blood pressure control of predialysis outpatients with ESRD who undergo routine hemodialysis in RS PKU Muhammadiyah Yogyakarta. This research is conducted by using a descriptive observational study design with prospective data collection method. Data analysis was performed to determine the profile of antihypertensive therapy use, antihypertensive medication therapy outcomes profile of the pre-dialysis blood pressure, and the influence of the patientsâ compliance level in antihypertensive medication towards the blood pressure control of pre-dialysis outpatients with ESRD who undergo routine hemodialysis in RS PKU Muhammadiyah Yogyakarta. The patient compliance level in taking antihypertensive drugs is assessed by questionnaire of Modified Morisky Scale (MMS). Based on the research results, the antihypertensive profile used was CCBs system (32,91%), loop diuretics (23,42%), AIIRA (15,82%), central Î± agonists (12,66%), ACEI (12,03 %), and Î² blockers (3,16%). Antihypertensive therapies applied single and combination therapy. Mono-therapy applied ACEI group (1,85%), CCBs (3,70%), and loop diuretics (1,85%). The most used antihypertensive combination are 3 application, they are a combination of the class of CCBs, AIIRA, and loop diuretics (16,67%). The outcomes profile of antihypertensive medication therapy based on the measurement results of predialysis blood pressure is the target of pre-dialysis blood pressure (<140/90 mmHg) can only be achieved by 3 patients, 2 patients are the compliance patients with the right choice and appropriate dose of antihypertensive therapy and 1 patient is a non-adherent patient with incorrect type and inappropriate doses of antihypertensive therapy. Most of hemodialysis patients have isolated systolic hypertension (ISH). The influence of the patientsâ compliance level in antihypertensive medication towards the blood pressure control of pre-dialysis outpatients, there are 19 patients (35,19%) in the category of non-adherent patients with a mean blood pressure is 168,40/ 91,95 mmHg, and 35 patients (64,81%) in the category of adherence with a mean blood pressure is 165,60/ 87,77 mmHg.